ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT CASH HOLDING PADA BANK UMUM YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2011-2015 - Silaen, Reni; Prasetiono, Prasetiono (Diponegoro Journal of Management, 2017)
This research aims to analyze the influence of  creditor’s payment period (CPP), debtor’s collection period (DCP), leverage (LEV), profitability (ROE), size (SIZE) and bank age(AGE) on cash holding in commercial banks listed on the Indonesian Stock Exchange.The population of this research is commercial banks listed on the Indonesian Stock Exchange period  2011-2015.  The types  of  data  used  are secondary  data  and  sample determination used the method of purpose sampling. The analytical tool used is panel data regression.The result shows that creditor’s payment period, debtor’s collection period and bank size has a significant effect on cash holdings, but leverage, profitability, and bank age does not has significant effect on cash holding.